Vitex trifolia L. (Botani, Metabolit Sekunder, dan Bioaktivitasnya) - Marina Silalahi; Revis Asra (Pro-Life, 2024)
Legundi, or Vitex trifolia (Verbenaceae), is an indigenous Indonesian plant that has been long used as traditional medicine. This study aims to explain the botany, secondary metabolites, benefits, and bioactivity of V. trifolia. The method used in this research is a literature review obtained online in 1996–2022, especially from Google Scholar, using the keywords V. trifolia, uses of V. trifolia, and bioactivity of V. trifolia. Description V. trifolia is a shrub or small tree; leaves are spread out with 1–5 leaves; compound flowers have a purple crown. The bioactivities of V. trifolia include anticancer, antiinflammatory, antimicrobial, antioxidant, antidiabetes mellitus, and hepatoprotective. The V. trifolia bioactivity as an anticancer is more prominent than the others. Some bioactive compounds against V. trifolia cancer are vitexicarpin, casticin, vitepyrroloids, rotundifuran, persicogenin, artemetin, luteolin, penduletin, vitexicarpin, chrysosplenol, vitexilactone, vitetrifolin, viterotulin, and vitexilactone. The compounds artemetin, casticin, and vitexilactone are associated with anticancer and antiinflammatory activity. Further study of anticancer compounds needs to be carried out so that the development of V. trifolia into a standardized herbal medicine, especially anticancer, can be developed.